Effects of functional tricuspid regurgitation on renal function and long-term prognosis in patients with heart failure. Issue 2 (February 2017) - Agricola, Eustachio; Marini, Claudia; Stella, Stefano; Monello, Alberto; Fisicaro, Andrea; Tufaro, Vincenzo; Slavich, Massimo; Oppizzi, Michele; Castiglioni, Alessandro; Cappelletti, Alberto; Margonato, Alberto
Abstract : Aims: Renal dysfunction is common in heart failure. Recent evidence suggests a pivotal role for systemic venous congestion and functional tricuspid regurgitation (FTR) in the pathophysiology of renal dysfunction. We investigated the role of FTR as a determinant of renal dysfunction and a predictor of long-term prognosis in chronic systolic heart failure patients. Methods and results: Four hundred and thirteen consecutive patients (mean age 74.2 ± 11 years) with chronic heart failure and left ventricular ejection fraction below 50% were enrolled. The FTR severity was quantified by transthoracic echocardiography. Renal function was evaluated with the estimated glomerular filtration rate measured by the simplified Modification of Diet in Renal Disease formula. The association between moderate/severe FTR and renal dysfunction, and its impact on heart failure episodes and overall mortality were also assessed. The median follow-up was 36 months (range 1–144 months). Through multivariate analysis, the interaction between moderate/severe FTR with tricuspid annular plane systolic excursion less than 16 mm was found to be an independent determinant of renal dysfunction [odds ratio 1.2, 95% confidence interval (CI) 1.1–1.5, P = 0.04]. Moderate/severe FTR (hazard ratio 1.3, 95% CI 1.2–2.7, P = 0.02) and tricuspid annular plane systolic excursion below 16 mm (hazard ratio 1.2, 95% CI 1.0–3.7, P = 0.01) were significantly related to the heart failure episodes. Moreover, the Kaplan–Meier analysis showed a worse outcome in patients with moderate/severe FTR (log-rank test 8.6, P = 0.003). Conclusions: The combination of significant FTR and right ventricular dysfunction, but not FTR and right ventricular dysfunction alone, is independently associated with renal dysfunction. The presence of significant FTR is related to an excess event rate of heart failure and has significant impact on outcome.